Next-generation molecular diagnostics - Aldape, Kenneth; Pfister, Stefan (Gliomas, 2016)
The classification of brain tumors is based on the time-honored tradition of histologic examination, coupled with clinicopathologic correlation, and is based on the fundamental importance of microscopic morphologic interpretation. Supplementation by immunohistochemical markers is of substantial value to distinguish related entities and to confirm morphologic impressions. The use of techniques such as fluorescent in situ hybridization (FISH) is also critical in specific situations. However, with these practices, it is clear that the use of state-of-the-art molecular techniques has great promise to add to classification to (1) reduce the subjectivity inherent in interobserver discordance, particularly with specific entities; and (2) elucidate the biologic diversity of entities that are not resolvable by routine methods. In this chapter, we discuss these possibilities, focusing on several tumor types affecting the central nervous system, including diffuse glioma and ependymoma.